Representasi Autistic Disorder dan Dampaknya dalam Novel Ikan Kecil Karya Ossy Firstan - Merissa Nedya Ananda; Yenni Hayati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Literary work is a place where the author can convey all his worries, both from within himself and from the surrounding environment. Through the novel Ikan Kecil by Ossy Firstan, a representation of autism is shown which can become new knowledge for some people who are still unfamiliar or taboo with autism. The type of research used in this research is literary research with a qualitative approach and descriptive method. The novel Ikan Kecil by Ossy Firstan presents forms of autism which can be recognized through the signs shown since the child was young, one of which is autistic disorder. The character Oleiro in the novel Ikan Kecil by Ossy Firstan has shown symptoms of autistic disorder since he was under one year old. These symptoms are increasingly visible along with the development and growth of the age of Oleiro's character. The impact caused by autism in the novel Ikan Kecil by Ossy Firstan with a family having autistic members is that there is an influence not only on the relationships among family members, but also on the surrounding environment.